2018
DOI: 10.1371/journal.pone.0197964
|View full text |Cite
|
Sign up to set email alerts
|

Developing a database for pedestrians’ earthquake emergency evacuation in indoor scenarios

Abstract: With the booming development of evacuation simulation software, developing an extensive database in indoor scenarios for evacuation models is imperative. In this paper, we conduct a qualitative and quantitative analysis of the collected videotapes and aim to provide a complete and unitary database of pedestrians’ earthquake emergency response behaviors in indoor scenarios, including human-environment interactions. Using the qualitative analysis method, we extract keyword groups and keywords that code the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…We also noted that experience of the earthquake in locations where damage occurred was an impetus to physically move. The salience of physical movement during earthquake shaking was reported by Bernardini et al (2016Bernardini et al ( , 2019 and Zhou et al (2018), who found that flight from buildings was the modal response in the earthquakes they examined and that there was relatively low compliance with official recommended actions. We also found that flight from buildings was highly prevalent, particularly in developing nations and that recommended actions like ''drop, cover and hold on'' were less prevalent than expected in nations where this action is emphasized.…”
Section: Overall Findings From Dyfi and Previous Literaturementioning
confidence: 87%
See 2 more Smart Citations
“…We also noted that experience of the earthquake in locations where damage occurred was an impetus to physically move. The salience of physical movement during earthquake shaking was reported by Bernardini et al (2016Bernardini et al ( , 2019 and Zhou et al (2018), who found that flight from buildings was the modal response in the earthquakes they examined and that there was relatively low compliance with official recommended actions. We also found that flight from buildings was highly prevalent, particularly in developing nations and that recommended actions like ''drop, cover and hold on'' were less prevalent than expected in nations where this action is emphasized.…”
Section: Overall Findings From Dyfi and Previous Literaturementioning
confidence: 87%
“…Using videotape obtained from closed circuit TV as well as evacuation simulations, these investigators examine the movements of people from the immediate experience of an earthquake to the end state of their physical movements. Of particular interest in relation to our study are observations that evacuation or movement is typically initiated at approximately MMI V (Bernardini et al, 2019) and that delay time, or the period in which persons attempt to define the situation, seeking cues from the environment or others before initiating movement, ranges from an average of 22s at intensity IV to 1.8 at intensity VIII, and 0 at IX (Zhou et al, 2018). In short, delay time decreases as intensity increases.…”
Section: Human Behavior In Earthquake Disasters: a Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The current demand for smart and safe city development makes emergency evacuation one of the hottest topics in fields including risk management, public health, and urban planning. In fact, over 22 thousand articles report emerging applications, discussions, and methodologies related to this topic within the last 5 years[7,8]. Most studies have focused on probabilistic risk models, simulations [9], evacuation drills [10], and socio-psychological aspects of documented disasters [11].…”
Section: Related Workmentioning
confidence: 99%
“…The primary cause of earthquake-related casualties is that people fail to evacuate to safe areas before the buildings they occupy collapse. Thus, the correct and efficient earthquake emergency evacuation is closely related to human safety and survival (Zhou et al 2018a(Zhou et al , 2018b.…”
Section: Introductionmentioning
confidence: 99%